Miniaturized overlapped LC phase delay line - Xin Guo (AIP Advances, 2014)
A novel miniaturized ultra-wide bandwidth (DC–35 GHz) LC phase delay line (PDL) based on overlapped meander inductors and air-bridge capacitors is proposed and fabricated. Two 45º and 90º PDLs were designed using a semi-lumped model, and the parameters were calculated and optimized based on transmission line theory and 3D simulations. The lengths of the 45º and 90º delay lines are 110 μm and 286 μm, respectively, which represent respective length reductions of 50% and 75% when compared with the corresponding conventional transmission lines. Over the entire operating band, the phase error is less than 0.6º for the 45º PDL and 2.5º for the 90º PDL. The return loss (S11) for both PDLs is better than 15.5 dB, while the insertion loss (S21) is less than 0.62 dB for both devices. Measured results show perfect consistency with the simulation results for these PDLs, and demonstrate the validity of the corresponding model.